PERAN GURUW MIDRAS DALAM SEJARAH PENDIDIKAN BUMIPUTERA DI AMBOINA PADA ABAD XIX - Belly Isayoga Kristyowidi (TANGKOLEH PUTAI, 2022)
This paper aims to explore the role of Guruw Midras for Bumiputera education in Amboina. This paper refers to the principles of historical research by utilizing Colonial archival sources, churches and newspapers in the nineteenth century. Through the education route, NZG envoys also gave birth to Midrash teachers who participated in the struggle to educate the Bumuputera people throughout the country. The dynamics of the socio-cultural development of the Amboina people cannot be separated from their role, the schools they care for play a significant role in the life of the congregation and evangelism in the Amboina region. The role of the Guruw Midras was to become a bridge between the Colonial and the government of the country and the people of the Country, this was proven by the additional duties besides their main duties being teachers and ushers in the congregation, their duty to record and report every event that occurred in the country where the Guru Midras was assigned. The emergence of the term Guru Midras can be accessed after the founding of Kam's Institute which was founded in the early XIX century, as well as being the beginning of the period in this paper. However, Guruw Midras' progress also depended heavily on Colonial political policies, one of which was Liberal political policies until the end of the nineteenth century which is also the end of the period in this paper.